Syria: A Showroom for Russia Latest Generation of Military Equipment - Yasmin, Leonando Arief; Dwiastuti, Ilmi (Jurnal Ilmu Sosial Indonesia (JISI), 2022)
Abstract. In 2011, a series of protest in MENA (Middle East and North African) region demanding a change of regime to democracy due to their outgrowing rage over the dictatorship government, poor living condition, and high-rates of unemployment ultimately leading to the Syrian Civil War. This paper aims to discuss the correlation of Russian entrance in the Syrian Civil War whether the war affected Russia’s defense industry through the ‘marketing effect’ it created in the battlefield. A Realist perspective is mainly used in this research paper to help uncover the benefits that Russia had gained in multiple spectrums since its entrance in the Syrian Civil War until the end of 2020, though, the discussion is mainly focuses on Russia’s arms sale industry and its growing partners in MENA after Russia’s entrance to the grand theatre.Keywords: Syrian Civil War, Russia, MENA, Arms sale. Abstrak. Pada tahun 2011, serangkaian protes di wilayah MENA (Timur Tengah dan Afrika Utara) menuntut perubahan rezim ke demokrasi karena kemarahan mereka yang semakin besar atas pemerintahan yang diktator, kondisi kehidupan yang buruk, dan tingkat pengangguran yang tinggi pada akhirnya mengarah pada Perang Sipil Suriah. Tulisan ini bertujuan untuk membahas korelasi masuknya Rusia dalam Perang Saudara Suriah, apakah perang tersebut mempengaruhi industri pertahanan Rusia melalui “marketing effect” yang ditimbulkannya di medan perang. Perspektif Realis terutamanya digunakan dalam penelitian ini untuk membantu mengungkap manfaat yang diperoleh Rusia dalam berbagai spektrum sejak masuknya dalam Perang Saudara Suriah hingga akhir tahun 2020. Meskipun demikian, diskusi ini terutama berfokus pada industri penjualan senjata Rusia dan mitra yang berkembang di MENA setelah masuknya Rusia ke teater besar.Kata Kunci: Perang Saudara Suriah, Rusia, MENA, Penjualan Senjata.